Utilisation of Sandal Waste From Home Industry in Kepuh Kiriman Village, Waru District, Sidoarjo Regency, As Coarse Aggregate Material in Mixing Materials For Paving Block Production - Ira Nur Ruwantari; Dyah Ratri Nurmaningsih; Yusrianti Yusrianti (Publikasi Indonesia, 2024)
Industrial activity is one of the factors that supports the growth of the economic sector. One industry that is currently proliferating is rubber sandal waste. This paper will use a mixture of rubber sandal waste as a coarse aggregate material. Sandal waste can be reused to produce products with a sale value, such as a mixture for making paving blocks. They were paving blocks that will be made using B-quality K-200. This paper aimed to determine compressive strength, water absorption, and SEM results. The method which is used in this research is descriptive quantitative. Paving Variations in sandal waste used in this study were 0%, 10%, 15%, and 20% of the volume of coarse aggregate. The optimal results produced are a 15% variation with a compressive strength age of 28 days with an average value of 18.8 MPa, a 10% variation with a compressive strength age of 7, and 14 days with an average value of 21.2 MPa and 21.8 MPa. The most optimal water absorption test results are at 10% variation with an average value of 5%. SEM test results with 15% and 20% variations showed a high air void content and microcracks spread in the specimen's topography. Meanwhile, at 0% and 10%, the spread of microcracks is insignificant, and the test object has a reasonably high density.